Adaptation of an additively manufactured reactor concept for catalytic methanation with in-situ tar co-reforming of biogenic syngas - Jakob Müller; Alexander Feldner; Simon Markthaler; Peter Treiber; Jürgen Karl (Chemical Engineering Journal Advances)
The methanation of biogenic syngas for GreenLNG production is a promising alternative for fossil gas. The market price of renewable methane is currently still too high to compete with fossil LNG. One of the reasons for that is the extensive gas cleaning that is necessary for the methanation of syngas from the thermochemical gasification of biomass. A main cost factor is the removal of tar components. As part of the Horizon Europe project CarbonNeutralLNG, we propose a 3D-printed methanation reactor, which makes use of the freedom in design gained by the additive manufacturing process in order to adapt the reactor design for the in-situ co-reforming of tars. The reactor uses heat pipes and a conically widened reaction channel to effectively control local temperatures, suiting the needs of the methanation reaction. A temperature hot spot near the inlet provides the necessary conditions (high temperature, a suitable catalyst and sufficient residence time) for the reforming of tar species, that are present in the syngas. Two reactor concepts are proposed. ADDmeth3.1 uses a dedicated internal channel structure that serves as a counter-current heat exchanger for the feed gas, whereas ADDmeth3.2 is optimized to fill the triangular footprint of a scalable reactor module as best as possible. Both designs were subject to a preliminary feasibility study, to ensure sufficient heat removal and a finite element analysis regarding structural stability was performed. Minimum safety factors against yielding of 3.53 and higher were achieved even without the internal diamond lattice support structure. The triangular modular reactor cell can easily be scaled up by connecting multiple cells in parallel, since the triangular shape can be extended efficiently into a honeycomb pattern.